What could we learn from SARS when facing the mental health issues related to the COVID-19 outbreak? A nationwide cohort study in Taiwan (2020)
There were several studies about the psychiatric and mental health issues related to the severe adult respiratory syndrome (SARS) outbreak in 2003, however, the association between SARS and the overall risk of psychiatric disorders and suicides has, as yet, to be studied in Taiwan. The aim of this study is to examine as to whether SARS is associated with the risk of psychiatric disorders and suicide. A total of 285 patients with SARS and 2850 controls without SARS (1:10) matched for sex, age, insurance premium, comorbidities, residential regions, level of medical care, and index date were selected between February 25 and June 15, 2003 from the Inpatient Database Taiwan’s National Health Insurance Research Database. During the 12-year follow-up, in which 79 in the SARS cohort and 340 in the control group developed psychiatric disorders or suicide (4047.41 vs. 1535.32 per 100,000 person-years). Fine and Gray’s survival analysis revealed that the SARS cohort was associated with an increased risk of psychiatric disorders and suicide, and the adjusted subdistribution HR (sHR) was 2.805 (95% CI: 2.182–3.605, p < 0.001) for psychiatric disorders and suicide. The SARS cohort was associated with anxiety, depression, sleep disorders, posttraumatic stress disorder/ acute stress disorder (PTSD/ASD), and suicide. The sensitivity analysis revealed that the SARS group was associated with anxiety, depression, sleep disorders, PTSD/ASD, and suicide after the individuals with a diagnosis of psychiatric disorders and suicide were excluded within the first year, and with anxiety, depression, and sleep disorders, while those in the first five years were excluded. In conclusion, SARS was associated with the increased risk of psychiatric disorders and suicide.